Living Donor Kidney Transplantation: How Far Should We Go? - Haberal, Mehmet A (Urology Journal, 2009)
Purpose: To describe the work that the Ba?kent University Faculty of Medicine has done to increase kidney donors’ number in Turkey and also to discuss the major effects that donor-organ shortage is currently having worldwide. Materials and Methods: From 1975 through 2003, our transplantation team at Hacettepe University Hospital and later at the Ba?kent University Transplantation Center (BUTC) performed 1451 kidney transplantations. Cadaver donation rates prior to and after the establishment of the National Coordination Center (NCC) were calculated and compared. Also, patient and graft survival rates for various groupings of transplantation types were compared. All statistical analysis was done using the log-rank test. Results: Of all the renal transplantations completed in Turkey from 1975 to January 2004, 20% were performed by our team in our center. For the years 1990 through 2003, the 1-, 3-, and 5-year patient survival rates in the first-degree-living-related kidney transplantation group were 96%, 93%, and 91%, respectively, and the corresponding graft survival rates were 93%, 84%, and 81%. In the second-degree living-related group, the 1-, 3-, and 5-year patient survival rates were 94%, 90%, and 87%, respectively, and the corresponding graft survival rates were 93%, 86%, and 84%. For living-unrelated transplantations, the 1-, 3- and 5-year patient survival rates were 93%, 90%, and 83%, respectively, and the corresponding graft survival rates were 83%, 78%, and 76%. In the cadaver-kidney transplantation group, the 1-, 3- and 5-year patient survival rates were 85%, 78%, and 70%, respectively, and the corresponding graft survival rates were 82%, 64%, and 53%. During this same period, the 1-, 3-, and 5-year graft survival rates for our cadaver donors and living donors older than 55 years of age were 80%, 52%, 46% and 88%, 69%, 61%, respectively. Conclusion: Vigorous efforts by our group at Ba?kent University and by other transplant surgeons across the nation have increased the numbers of transplantations performed each year. As well, since the NCC was established in 2001, the number of cadaver-kidney transplantations has more than doubled. The initial results with this new nationwide organ-sharing system are promising, and there is every indication that this approach will continue to raise the number of transplant operations performed across Turkey each year. We suggest that Turkish citizens should consider changing our national policies on organ donation. Opt-out policies can increase the pool of cadaver-organ transplants. In addition, to increasing cadaver donation, we feel that living-related donation restricted to first- and second-degree relatives and acceptable non-blood-related donors (such as spouses) is the best path to expanding kidney transplantation worldwide.